Analysis of Inter-radicular Septum in the Treatment Planning for the Placement of Immediate Maxillary Molar Implants: A Retrospective Cone Beam CT Study - Pradnya Karmarkar; Amit Mhapuskar; Darshan R. Prasad Hiremutt; Isha Kale; Akash Bhokare (Wolters Kluwer Medknow Publications, 2024)
Background: Our study highlights the assessment of inter-radicular septum (IRS) on cone beam CT (CBCT) as an important pretreatment tool for immediate maxillary molar implant (IMI) placement. The aim of our study was to evaluate the suitability of the IRS of the maxillary first and second molars on CBCT to receive IMI. Objectives: The objectives of our study were to measure and compare IRS dimensions of the first and second molars and to assess the suitability of maxillary first and second molars to house an immediate implant. Method: In total, 200 CBCT scans (100 each for first and second molars) that display IRS completely were selected for the study. The IRS was analyzed in all three dimensions. Then, the percentage of first and second maxillary molars that were suitable to receive an IMI based on Smith and Tarnow's classification was calculated. Results: It was found that 89% first and 71% of second molars were eligible sites for IMI. Conclusion: Careful evaluation of IRS will lead to a better prognosis for IMI.